PENERAPAN STANDAR AKUNTANSI ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) DALAM MENYUSUN LAPORAN KEUANGAN - Hetika Hetika; Nurul Mahmudah (Politeknik Ubaya, 2018)
Small and Medium Enterprises (SMEs) is a business that contributes in economic development in Indonesia, because the sector of SMEs is proven to absorb labor and increase in people’s income. The large potential of SMEs is expected to support economic development in Indonesia. SMEs are managed and developed properly will certainly realize a tough business sector. A robust SMEs sector must be supported with good administration. One of the problems faced by the perpetrators of SMEs is the administrative problems associated with the listing of finances in its business. This study aims to analyze whether the understanding and application of basic concepts of accounting can facilitate the perpetrators of SMEs in the City of Tegal to follow the financial statements in accordance with SAK EMKM. The sample of this research is UMKM in Tegal city taken by purposive sample technique. Methods of data collection in this study used the method of observation with questionnaires and direct interviews with respondents. This study uses descriptive analysis techniques to determine the application of accounting in panyusunan financial reports of SMEs in the city of Tegal. The results showed that the application of basic concepts of accounting through the basic equation of accounting can facilitate the perpetrators of SMEs in the City of Tegal to prepare financial statements in accordance with SAK EMKM.